METODE PELAKSANAAN KONSTRUKSI PILE CAP PADA PROYEK PEMBANGUNAN GEDUNG RITA SUPERMALL DAN SWISS BEL HOTEL DI PURWOKERTO - , ARUM SEPTINAWATI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Pile cap is a tread that is usually of reinforced concrete that serve to unite a group of piles and spread the load of the structure above it. Because the role of pile cap is very important the method used and the implementation on the ground in terms of deciding to make it happen. In this implementation study aims to analyze the pile cap construction methods, use of tools and materials, and quality control of steel reinforcement and concrete in the construction of pile cap. The construction of pile cap based on the method of pile cap structure, fabrication method and casting methods that have been planned in the project. In the implementation of the field consists of excavation with excavators and workers, cutting pile head, attach the formwork brick, flooring work, reinforcement and casting. The results of the field observations were analyzed by comparison with the theories and methods. The results of an analytical study on the implementation of the pile cap construction work in accordance with the theories and methods planned. The use of tools and materials on pile cap construction in accordance with the schedule and needs. Implementation of quality control of concrete reinforcing steel and concrete in accordance with the groove that has been required and in accordance with the quality specifications.